STRUCTURAL COMPONENTS OF RESISTANCE TO COMBAT-PSYCHOLOGICAL TRAUMA IN LAW ENFORCEMENT – COMBATANTS - Kolesnychenko, Oleksandr (PSYCHOLOGICAL JOURNAL, 2018)
The article presents the results of an empirical study of the factor structure of resistance to combat psychological trauma among unsafe type law enforcement officers with a different level of trauma of combat experience. The distinguished six-factor structure of resistance to combat psychological trauma among ascending law enforcement officers with a low level of trauma of combat experience: the first factor is indicated as: “Limited professionalism”; The second factor is designated as: “Self-relation − as a source of change”; the third factor is designated as “Socially active life position”; the fourth factor is “Self-incrimination as a manifestation of uncertainty in one’s ability to overcome dangerous situations”; the fifth factor was labeled “Warning Hazard” (belief in the ability to avoid danger); The sixth factor is designated as “Image (conditional) courage”. Ascending law enforcement officers with an average level of trauma of combat experience, the six-factor structure of resistance to combat psychological traumatization is as follows: the first significant factor is “Acute need for help”; the second factor is “Acute need to set the structure of the situation, as opposed to the feeling of own powerlessness, loss of control”; the third factor “Egocentricity as a reaction to frustration”; the fourth factor is “Helplessness”; the fifth factor is “disorientation”; The sixth factor, “The desire to assert itself.” The structure of resistance to trauma among ascending law enforcement officers with a high (acquired) level of trauma of combat experience combines both the poles of its development: the first factor “Perception of one’s own competence as unique”; the second factor is “The internality of professional achievements”; the third factor “Mental intolerance”; the fourth factor is the “inferiority complex”; the fifth factor is “The desire to return to family measured life"; the sixth factor is “Mental (not directed at external adaptation) adaptation.” It has been studied that ascending types of law enforcement officers increase the load on their own resources with increasing levels of psycho-traumatic combat experience. So, due to lack of professional identity and the formation of professionally important qualities, the prospect of participating in hostilities actualizes the memories of the stressful situation, increases anxiety and self-doubt. Fear of not responding to the expectations of colleagues closes for representatives of this group the opportunity to use the help of their professional group and take over their experience, with an average level of psycho-traumatic combat experience leads to the need to adapt their “civilian” experience to overcome emotionally similar combat situations. With a high level of psycho-traumatic combat experience, the right guard has a forced decrease in all activities not related to survival; professional skills continue to be formed at the expense of general competence, and the desire to gain access to the resources of a professional group, to earn its approving attitude pushes for desperate, courageous actions.